Building sustainability and community involvement at Tangguh Waste Bank - Hermahayu Hermahayu; Akhmad Liana Amrul Haq; Rayinda Faizah; Aning Az Zahra; Laili Qomariyah (Community Empowerment, 2024)
Tangguh Waste Bank is located in Wonosuko Hamlet, Tegalrejo Village, Tegalrejo District, Magelang Regency. The Tangguh Waste Bank has recently been established, so there are several shortcomings, including a lack of understanding of community ecoliteracy, which hinders community involvement in managing waste more broadly. To overcome these obstacles, community service activities were carried out with program targets for waste bank administrators based on a green economy. The implementation of the service uses a participatory approach method, focusing on: 1) socialization of the management of waste banks and reading corners, 2) training and guidance on the management of waste banks and reading corners, 3) outbound management of waste banks and the community to increase cooperation and cohesiveness between members. The results achieved through this activity include the preparation of a one-year work program for Tangguh Waste Bank management, equipped with a timeline and the person responsible for each sub-work program. Additionally, the level of management participation in activities increased by 53%.